Relationship between performance indicators and the success in professional football - Castellano, J. (Revista Iberoamericana de Psicologia del Ejercicio y el Deporte, 2018)
This paper studied the relationship between performance and success of professional football teams. Teams` performances of the First (L1) and second (L2) division of Spanish football leagues in consecutive seasons, 2013-14 (T1) and 2014-15 (T2), were analyzed. For assessing performances, they were included the following keys (IR): a) as indicators of result (IRr) were annotated goals scored and conceded, and final behaviours like crosses and shots; and, b) as indicators of process (IRp) were recorded the game volume (passes and efficacy), collective use of the space, distance covered and variables involving set pieces. The success of the teams was valued considering the points scored at the end of the championship. The main results of the study were: 1) IR had different degrees of relationship with the success of the teams, being the IRr mostly related with to the points scored; 2) the relation between IRr or IRp and final accumulated points varied depending on the category of the teams, more offensive indicators in L1 and more defensive in L2 when were compared with the final output; and, 3) the IR unchanged from one season to another. This study supports the conclusion that use systematically IR (outcome and process) can be helpful in professional football, for knowing the particular performance that can approach a team to the success in a given league. Coaches could use this information, once contextualized to the team and league where they participate, in order to propose intervention`s strategies that optimize the performance of the team.